Explaining Local Policy Agendas - B. Mortensen, Peter. author. aut Link
XII, 194 p. 31 illus.
Keywords: This is the first large scale empirical test of a theory of what determines the content of the governmental agenda. With hundreds of governments to compare, the authors have a unique opportunity to explore the determinants of government attention, not just to describe it. The results should be of interest to a wide range of scholars. Anyone who wants to know why governments do what they do should read this book. - Frank R. Baumgartner, Richard J. Richardson Distinguished Professor of Political Science, UNC at Chapel Hill Peter B. Mortensen, Matt W. Loftis, and Henrik Bech Seeberg have written an important book, both for the study of policy agendas and for local politics. The subnational case study fills a crucial gap in our understanding of the world of agenda-setting behind national politics. It also provides a unique set of data to test out classic questions in urban politics and policy. - Peter John, Professor of Public Policy, King’s College London This inspiring book investigates classic questions in political science by means of innovative analyses of local government agendas. The book is essential reading for local government students and scholars. It provides important knowledge about how political systems at the local level work, and the rigorous analyses profoundly demonstrate how local level institutions and politics can and should be studied. - Signy Irene Vabo, Professor of Political Science, University of Oslo Building on hundreds of thousands of systematically collected and content-coded local policy agenda observations, this book examines – theoretically and empirically - the policy agenda effects of four central aspects of any political system: the institutions that structure politics; the problems confronting the political system; the occurrence of regular elections; and the actors navigating the political system. Peter B. Mortensen is Professor of Political Science at Aarhus University, Denmark. Matt W. Loftis is Associate Professor of Political Science at Aarhus University, Denmark. Henrik B. Seeberg is Associate Professor of Political Science at Aarhus University, Denmark.